Myofascial Pain and Dysfunction.2.vol. : The Trigger Point Manual.The Lower Extremities - TRAVELL, Janet G; SIMONS, David G (Williams and Wilkins, 1992)
A thorough understanding of what myofascial pain actually is, and provides a unique and effective approach to the diagnosis and treatment of this syndrome for the lower body muscles.
Keywords: Foot; Leg; Ankle; Knee; Thigh; Hip; Lower Torso